APPLICATION OF SHARIA MARKETING STRATEGIES AT PT AUVA EQTENA NAHDHA TO INCREASE SALES - Rahmah, Nanda; Hasan, Nurul (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
This study aims to analyze the application of sharia marketing strategies at PT. Auva Eqtena Nahdha and their effect on sales growth. The method used in this study is descriptive qualitative through case studies. Data collection was carried out through observation and document collection from company management. The results of this study indicate that the company regularly applies sharia marketing principles, such as trust, honesty, clear communication, and marketing innovation based on Islamic values. The implementation of this strategy not only creates a positive image for the company but also has a significant impact on increasing sales and customer loyalty. These results show that Islamic marketing is an effective strategy for achieving blessings while ensuring business continuity. This study suggests increasing education about Islamic values and innovation in digital marketing so that companies can continue to improve their competitiveness.